2016
DOI: 10.1371/journal.pone.0163334
|View full text |Cite
|
Sign up to set email alerts
|

Parental Age of Onset of Cardiovascular Disease as a Predictor for Offspring Age of Onset of Cardiovascular Disease

Abstract: ObjectiveThe risk for cardiovascular disease (CVD) is higher for individuals with a first-degree relative who developed premature CVD (with a threshold at age 55 years for a male or 65 years for a female). However, little is known about the effect that each unit increase or decrease of maternal or paternal age of onset of CVD has on offspring age of onset of CVD. We hypothesized that there is an association between maternal and paternal age of onset of CVD and offspring age of onset of CVD.MethodsWe used the F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 43 publications
1
5
0
1
Order By: Relevance
“…Overall, the RR was 3.79 under the age of 65 and 2.21 over the age of 65; the HR for ischemic stroke was 5.45 under the age of 65 and 2.47 over the age of 65. Additional implicit information from this data, which supports the same conclusion, is listed in Allport et al (2016) The heritability patterns for these diseases are summarized in Table 3. There is qualitative and, increasingly, quantitative knowledge about the progressively declining heritability of these diseases at ages above 50, as well as the decreasing associated familial and GWAS predictive power; see Table 1.…”
Section: Lods With Decreasing Heritability With Agesupporting
confidence: 72%
“…Overall, the RR was 3.79 under the age of 65 and 2.21 over the age of 65; the HR for ischemic stroke was 5.45 under the age of 65 and 2.47 over the age of 65. Additional implicit information from this data, which supports the same conclusion, is listed in Allport et al (2016) The heritability patterns for these diseases are summarized in Table 3. There is qualitative and, increasingly, quantitative knowledge about the progressively declining heritability of these diseases at ages above 50, as well as the decreasing associated familial and GWAS predictive power; see Table 1.…”
Section: Lods With Decreasing Heritability With Agesupporting
confidence: 72%
“…Although the highest cardiovascular risk was associated with a maternal history at age < 50 years and a paternal history at age < 55 years, no substantial differences were seen between maternal and paternal positive CVD history [16]. In a Dutch cohort study, a particularly high incidence of CVD was revealed in people with parental onset of MI before age 70, with maternal history of MI before age 60 being the strongest predictor of CVD incidence [17].The offspring age of onset of CVD is significantly associated with both maternal and paternal age of CVD onset [18]. Nevertheless, data regarding the role of a family history of CVD that includes relatives other than parents or the number of affected family members are scarce.…”
Section: Discussionmentioning
confidence: 96%
“…Although the highest cardiovascular risk was associated with a maternal history at age <50 years and a paternal history at age <55 years, no substantial differences were seen between maternal and paternal positive CVD history [16]. In a Dutch cohort study, a particularly high incidence of CVD was revealed in people with parental onset of MI before age 70, with maternal history of MI before age 60 being the strongest predictor of CVD incidence [17].The offspring age of onset of CVD is signi cantly associated with both maternal and paternal age of CVD onset [18]. Nevertheless, data regarding the role of a family history of CVD that includes relatives other than parents or the number of affected family members are scarce.…”
Section: Discussionmentioning
confidence: 98%